Integrating Scientific Principles with Character Development in the Student Worksheet on Change in Matter - Mauliza, Mauliza; Nurhafidhah, Nurhafidhah; Oktaviani, Coryna (Jurnal Tadris Kimiya, 2023)
Integration of scientific principles with character development in the student worksheet on change in matter is crucial for fostering a holistic understanding of chemistry, aligning academic knowledge with ethical considerations, and cultivating a well-rounded educational experience. The aim of this research is to develop character-integrated teaching materials in science subjects that are suitable for use as learning media. The development of character-integrated teaching materials in science subjects uses a 4D model, consisting of four stages (define, design, develop, and disseminate). Teaching materials developed are in the form of student worksheets. Data collection technique used a questionnaire with several instruments, which are material and media expert validation instruments, student worksheets eligibility instruments, and interview instruments. Analysis of the data using the calculation of the average, percentage, coefficient of validity, and descriptively. The results of the analysis of material expert validation data, obtained a validity level of 0.825 with a very valid category. Similarly, the results of the analysis of media expert validation data, obtained a validity level of 0.735 with a very valid category. The results of the analysis of the feasibility questionnaire filled in by the teacher obtained a score of 86.25% with a very decent category. It can be concluded that the student worksheets developed is very suitable to be used as a science learning media.